EFFICACY OF SELECTED MOBILITY EXERCISES AND PARTICIPATION IN SPECIAL GAMES ON FUNCTIONAL ABILITIES AMONG INTELLECTUALLY DISABLED CHILDREN OF UNDER 18 AGE GROUPS (Fiep Bulletin - online, 2018)
The purpose of the study was to find out the efficacy of selected mobility exercises and participation in special games on functional abilities among intellectually disabled children of age group under 18, Thirty male students who were studying in Balar Kalvi Nilayam and YMCA College Special School, Chennai, acted as subjects for the study. They were only mild and moderate in intelectual disability. These students did not undergo any special training or coaching programme apart from Their regular routine physical activity classes as a parto f the curriculum in the school. They were attached at random, based on age in which 30 belonged to under 18 age group, Which was divided into three equal group of tem for each experimental treatment. 10 students ( Treatment group I) underwent calisthenics and especial games participation, 10 students ( Treatment group II) underwent yoga and special games participation, 10 students ( Treatment group III) underwent yoga and special games Participation. The subjects were tested on selected criterion variables prior (pre test) and after twelve weeks of training (post test). The pre and post test data collected from three groups on functional abilities ( Self-care, Learning, Independent living), were statistically examined for significant difference, by applying The analysis of covariance (ANACOVA). To find out signigicant improvement due to the training on functional abilities. Whenever na 'F' ratio for adjusted test was found to be signigicant for adjusted post test means, Scheffe's test was found to be significant for adjusted post test means, Scheffe's test was followed as a post hoc test to determine which of the paired mean diferences was signignificant. The result of the study showed that among under 18 age groups there was a significant improvement on selected criterion variables such as, Self-care, Independent Living due to mobility exercises and participation in especial games, however no significant diferences among the groupes.